Women's underrepresentation in business-to-business sales: Reasons, contingencies, and solutions - Aline Isabelle Lanzrath; Christian Homburg; Robin-Christopher M. Ruhnau (Journal of the Academy of Marketing Science, 2023)
Sales faces the second-largest gender gap of any corporate function, with women's underrepresentation even more pronounced in business-to-business (B2B) sales and at higher hierarchical levels. Concurrently, the call for a more gender-diverse sales force is gaining momentum for social and economic reasons, moving the question of how to attract and promote women in B2B sales to the top of sales managers' agenda. Using an inductive approach, we uncover male-centricity of communication and job structures in B2B sales as the underlying reasons deterring women from entering and advancing in B2B sales. Specifically, male-centricity implies a misfit between B2B sales and women's self-conception and needs. By deriving contingencies of these relationships, we offer solutions to women's underrepresentation in B2B sales by showing, for example, which sales positions are less prone to signal or create a misfit to women and what gender-inclusive resources sales departments can provide and saleswomen can build.
Keywords: 330; Business-to-business sales; Sales management; Sales diversity